Helmholtz resonator-based acoustic metamaterials enabling broadband asymmetric sound absorption and ventilation - Deshi Meng; Lijun Li; Zhenhua Wu (Journal of Low Frequency Noise, Vibration and Active Control, 2023)
Acoustic metamaterials with both ventilation and broadband asymmetric absorption have demonstrated great scientific significance and promising applicability. In this work, we design an asymmetric absorbing cell (AAC) consisting of a pair of detuned Helmholtz resonators (HRs) connected by sound channels that allows airflow with a ventilation ratio (ventilation area divided by sound incidence area) of 40%, which can achieve near-perfect sound absorption in the operating frequency range when sound waves are incident from the left port. However, when incident on the right port, the acoustic absorption coefficient does not exceed 40% at most, so asymmetric absorption is achieved. In addition, we form parallel three-cell asymmetric absorber (PTAA) by paralleling three AACs, which have broadband asymmetric absorption compared to AAC. Furthermore, we design multi-asymmetric absorber (MAA), which can achieve broadband asymmetric absorption range from 1000 Hz to 1750 Hz, and also allow air circulation. Moreover, experimental validation is conducted to demonstrate the effectiveness of fabricated MAA by 3D printing technology. Our designs open potential possibilities for developing ventilated functional devices capable of absorbing sound asymmetrically.